The Implementation of Artificial Intelligence in Human Resources Management - Shouran, Zaied; Ali, Assoc. Prof. Dr. Dhakir Abbas (AIBPM Publisher, 2024)
This research examines the implementation of artificial intelligence (AI) in HRM functions like recruitment, training, and performance management. It suggests that AI can improve recruitment processes, enhance training and development programs, and optimize performance management by providing more accurate feedback. However, it also highlights challenges such as data privacy and security concerns, job displacement, and the need for human oversight and accountability. The paper discusses the implications for the workforce, organizations, and society and suggests future research to address these issues, ensure human oversight, address social and economic inequalities, develop more effective AI training and development programs, and develop more effective AI governance frameworks. The paper concludes that AI has the potential to impact the future of work in HRM practices significantly, but its implementation must be subject to responsible and ethical governance and regulation to maximize its benefits and mitigate its negative impacts.